Representation of Islamic Morality in The Comic Al Fatih 1453 - Nila Alfa Fauziyah; Imam Maksum (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2020)
Morality is a crucial issue to be studied in the current era of globalization. Therefore, the researcher chose the comic Al Fatih 1453 as research material because it can be used as an example of learning, especially for children who are in the learning process to practice Islamic moral values in the form of mah easy morals in everyday life as well as to introduce the figure of Muhammad Al Fatih. Therefore, this study examines: (1) How are the meanings of signs, objects, and interpretants conveyed in the comic Al Fatih 1453? (2) What Islamic morality is contained in the comic Al Fatih 1453? To describe the two problems, the researcher uses a qualitative approach and the type of research used in this research is the type of Media Text Analysis research with Charles Sanders Peirce's semiotic analysis model. The results of this study indicate that (1) the delivery of the sign (representamen), object, and interpretation of meaning (interpretant) contained in the comic Al Fatih 1453 can be seen through visual illustrations (pictures) and text (writing) which will be used as research data. Then it will be described using Charles Sanders Peirce's semiotic analysis model. (2) The morality of Islam contained in the comic Al Fatih 1453 is a maheasy character, that is, a commendable character. Maheasy morals are morals that reflect the teachings of the Prophet Muhammad, in the form of asceticism, endeavor, friendship, gratitude, and prayer.